2003
DOI: 10.1128/cmr.16.1.129-143.2003
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Human Viruses in Coastal Waters

Abstract: This review addresses both historical and recent investigations into viral contamination of marine waters. With the relatively recent emergence of molecular biology-based assays, a number of investigations have shown that pathogenic viruses are prevalent in marine waters being impacted by sewage. Research has shown that this group of fecal-oral viral pathogens (enteroviruses, hepatitis A viruses, Norwalk viruses, reoviruses, adenoviruses, rotaviruses, etc.) can cause a broad range of asymptomatic to severe gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
165
1
13

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 243 publications
(182 citation statements)
references
References 144 publications
3
165
1
13
Order By: Relevance
“…There are no currently mandated tests for viral indicators in recreational and shellfish harvesting waters, in part because of the lack of suitable available assays. However, bacterial indicators alone are inadequate predictors of viral pathogens, which have been shown to sometimes be present even in waters with low bacterial indicator concentrations; reports from numerous locations, including the study area reported here (11,12,22), show an absence of a significant quantitative relationship between indicator bacteria and viral pathogens, as reviewed by Griffin et al (8).…”
mentioning
confidence: 67%
See 4 more Smart Citations
“…There are no currently mandated tests for viral indicators in recreational and shellfish harvesting waters, in part because of the lack of suitable available assays. However, bacterial indicators alone are inadequate predictors of viral pathogens, which have been shown to sometimes be present even in waters with low bacterial indicator concentrations; reports from numerous locations, including the study area reported here (11,12,22), show an absence of a significant quantitative relationship between indicator bacteria and viral pathogens, as reviewed by Griffin et al (8).…”
mentioning
confidence: 67%
“…About 37% of the United States population resides in coastal areas, with about 1.0 ϫ 10 10 gallons of wastewater released into rivers and seas from outfalls and storm drains per day (8). Before their release, wastewaters are not always treated to remove viruses, and storm water is usually not treated at all (24).…”
mentioning
confidence: 99%
See 3 more Smart Citations